The Implementation of a Deep Learning Approach Using QR Code–Based Learning Media to Enhance High School Students’ Academic Performance in Kinematics - Lusiani; Dhion Meitreya Vidhiasi; Supriyanto (Jurnal Penelitian Pendidikan IPA, 2026)
Educators and schools might seek the availability of adequate learning resources. The learning resources for kinematics at SMAN 1 Bawang are limited in quantity and diversity. Previous observations indicated that most students relied on rote memorization of formulas, which led to difficulties when applying them to problems. Consequently, the author is motivated to investigate the application of the Deep Learning Approach utilizing QR Code learning media, aiming to assess the enhancement of high school students’ learning outcomes in kinematics who engaged with this method, as well as to compare the improvement in learning outcomes between the experimental and control classes. The research employed a quasi-experimental design with a pretest–posttest control group. The research population comprised students at SMA Negeri 1 Bawang, with the sample consisting of students from grades XI VI and XI VII. The sampling technique employed was cluster random sampling. The instruments utilised were assessments and surveys to evaluate learning outcomes and student feedback. The statistical test yielded a significant value. The two-tailed p-value of <0.05, specifically 0.00, indicates the rejection of H₀. Consequently, it is concluded that a difference exists in the learning outcomes of kinematics material between pretest and posttest scores in the experimental class, which utilised a deep learning approach with QR code media. The data reveal an improvement from a pretest score of 47.37 to a posttest score of 77.73, reflecting a 30.36% increase. The implementation of a deep learning strategy utilising QR code media demonstrates a significant enhancement in learning outcomes relative to traditional classroom instruction. The research suggests creating an interactive digital module that combines printed materials with actual experimental videos or virtual simulations, accessible via QR codes in each sub-chapter of the kinematics content.